Applicability of computed tomography and rhinoscopy in the diagnosis and monitoring of the treatment of epistaxis in a dog - Matos, Matheus Daudt; Toledo, Flávia Silva Raja Gabaglia; Rocha, Luana Menezes; Bendas, Alexandre José Rodrigues (Brazilian Journal of Veterinary Medicine, 2025)
Epistaxis is defined as bleeding from the nasal cavity and can be related to systemic causes leading to coagulation disorders, most commonly hemoparasitosis, or to localized changes in the nasal cavity itself (e.g., intranasal neoplasms). Transmissible venereal tumors (TVT) are malignant round cell neoplasms characterized by an anomalous proliferation of tumor cells disseminated mainly by direct contact between animals. Although transmitted sexually, transmission through contact with mucous membranes and skin tissue can also occur, including the nasal cavity. Although rare, it can have significant clinical implications because it is difficult to diagnose. The diagnosis is made by physical examination, imaging tests (computed tomography and rhinoscopy), and histopathological analysis, which is the gold standard. Treatment is based on the use of chemotherapeutic agents, with vincristine as the drug of choice. This study reported a case of intranasal TVT in a 4-year-old French bulldog and addressed its clinical characteristics, diagnosis, and treatment. It also reported the importance of early recognition of the condition and changes in imaging tests to better understand and manage this atypical presentation.